Antecedents of Business Performance through Professional Management in Family Property Businesses in Jabodetabek - Daniel Yuwono; Bahtiar Usman; Deasy Aseanty (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study aims to determine the role of Professional Management as a variable in mediating Strategic Planning, Readiness for Change, and Family Involvement towards Business Performance in a family property business. The analytical method used to answer this research problem is Structural Equation Modeling (SEM), where the data processing uses the Analysis of Moment Structures (AMOS 22) program. The number of samples in this study was 250 respondents from Senior Staff up to Top Management Level. The results of this study found that there were two hypotheses that had an unsupported influence: the Readiness for Change variable on Professional Management and the Readiness for Change variable on Business Performance through Professional Management. The remaining hypotheses indicated that Strategic Planning, Readiness for Change, and Family Involvement supported Business Performance. The Strategic Planning and Family Involvement hypothesis supported Professional Management. This study contributes both theoretically and practically by demonstrating that Professional Management plays a critical role in transforming organizational antecedents into business performance. The findings highlight a behavioral–structural gap in family firms, where readiness for change does not automatically translate into formal governance mechanisms, providing important implications for the professionalization and sustainability of family businesses.   Keywords: Strategic Planning, Readiness for Change, Family Involvement, Professional Management, Business Performance.